Factors affecting junior high school students' interest in continuing to Vocational High School in Magelang District - Dian Purnama Sari; Sudji Munadi (Jurnal Pendidikan Vokasi, 2017)
This research aimed to reveal the effect of junior high school (SMP) students' self-knowledge, academic achievement, counseling and guidance service, school (SMK) image to their interest in continuing their education to vocational high school (SMK) in Magelang District. The population of the research was all of grade IX SMP students, with 387 students as samples. The data were collected using questionnaires and documentation and were analyzed using descriptive and regression analysis. The result of this study shows that: (1) the interest of SMP students' to continue their study to SMK is very high; (2) there is a positive and significant contribution of students' self-knowledge, academic achievement, counseling and guidance service, school (SMK) image; to SMP students' interest in continuing their study to SMK. The r2 values are 0.338; 0.063, 0.226, and 0.155, respectively; and (3) the four variables collectively have a positive and significant contribution to the interest in continuing the study to SMK in Magelang District with an r2 value of 0.440.